Travel mode choice of the commuters in Temuco, Chile: The association of personal factors and perceived built environment - Mohammad Paydar; Asal Kamani Fard (Transportation Research Interdisciplinary Perspectives)
Increasing the minimal rate of physical activity on commuters’ work travels might benefit their public health by promoting more active travel options. Most commuters in Temuco, a medium-size city in southern Chile, work in the city center, which has led to congestion on most of the roadways that connect to the city’s center during rush hour. This study aimed to investigate the relationships between Temuco commuters’ various modes of transportation and the relevant personal, social, and built environment factors. The objective was examined using 644 respondents from six neighborhoods and the data was analyzed using multinomial logistic regression for both actual and preferred mode choice of the commuters. There is a trend in this city toward greater usage of bicycles and a decreased use of public transportation. In addition, the findings show that several features such as such as age, ethnic background, bicycle ownership, walking attitude, and attitude toward a private car, are associated with the commuters’ actual and preferred mode choice in this city. The desired usage of walking is likewise favorably correlated with role models, and actual and preferred walking was also found to be correlated with two recognized lifestyle factors. When it comes to perceived built environment features that promote public transportation and active travel, accessibility is by far the most significant. These data could be used by the city’s urban and transportation officials to promote more environmentally friendly modes of transportation, such as public transportation and active travel, as alternatives to private vehicles for commuters’ everyday trips.